2022
DOI: 10.1007/s10644-022-09396-2
|View full text |Cite
|
Sign up to set email alerts
|

Does China’s green economic recovery generate a spatial convergence trend: an explanation using agglomeration effects and fiscal instruments

Abstract: China’s urbanization process has entered a period of rapid development, and cities have become key to driving regional economic development. This paper uses data from 286 cities in China in the period 2005–2018 to construct an urban economic growth quality index system and examine the influence of spatial factors on the convergence trend of China’s urban economic growth quality. It is found that there is a β absolute convergence trend of economic growth quality in Chinese cities across t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The major findings confirmed that investment can bring sufficient capital to green project leading to sustainable activities of China’s heavy-polluting industries. Kong et al ( 2022 ) discovered the direct positive impact of fiscal instruments on efficient green economic recovery of China. In a fresh study, Naseer et al ( 2022 ) employed the Analytical Hierarchical process (AHP) to evaluate aspects of green economic efficiency in China.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The major findings confirmed that investment can bring sufficient capital to green project leading to sustainable activities of China’s heavy-polluting industries. Kong et al ( 2022 ) discovered the direct positive impact of fiscal instruments on efficient green economic recovery of China. In a fresh study, Naseer et al ( 2022 ) employed the Analytical Hierarchical process (AHP) to evaluate aspects of green economic efficiency in China.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to the spatial spillover effects facilitated by the digital economy, the efficiency gap in green economy development among Chinese provinces is gradually narrowing. This convergence demonstrates “Club Convergence” characteristics, exhibiting positive spatial correlation and a strong degree of spillover [ 43 ]. The flow of production factors, resource sharing, and capital enabled by the digital economy promotes the spatial spillover of green technologies between regions, facilitating the sharing and development of green technological innovation among different areas.…”
Section: Theoretical Mechanism and Hypothesesmentioning
confidence: 99%
“…Furthermore, we briefly survey and summarize previous research related to China's economic recovery, which has a very high reference significance for the topic of this paper. More specifically, some scholars have explored the role of government in the process of China's economic recovery (Kong et al, 2022; Yang et al, 2021), while other researchers have targeted what China's economic recovery could bring to the world (Soomro et al, 2021; Wang & Zhang, 2021). Other related contents about economic recoveries, such as recovery policies and the recovery of specific provinces, are also the focus of existing scholars' research (Fu et al, 2020; Jiang et al, 2021; Wang, Wang, & Chang, 2022; Wang, Zhang, et al, 2022; Yang et al, 2020; Zhang & Zheng, 2020).…”
Section: China's Ger In the Post‐epidemic Eramentioning
confidence: 99%